Effectiveness of a High-Fidelity Simulation-Based Training Program in Managing Cardiac Arrhythmias in Children: A Randomized Pilot Study. Issue 6 (June 2019) - Bragard, Isabelle; Farhat, Nesrine; Seghaye, Marie-Christine; Karam, Oliver; Neuschwander, Arthur; Shayan, Yasaman; Schumacher, Katharina
Abstract : Objectives: Pediatric cardiac arrest is a rare event. Its management requires technical (TSs) and nontechnical skills (NTSs). We assessed the effectiveness of a simulation-based training to improve these skills in managing life-threatening pediatric cardiac arrhythmias. Methods: Four teams, each composed of 1 pediatric resident, 1 emergency medicine resident, and 2 pediatric nurses, were randomly assigned to the experimental group (EG) participating in 5 video-recorded simulation sessions with debriefing or to the control group (CG) assessed 2 times with video-recorded simulation sessions without debriefing at a 2-week interval. Questionnaires assessed self-reported changes in self-efficacy, stress, and satisfaction about skills. Blinded evaluators assessed changes in leaders' TSs and NTSs during the simulations and the time to initiate cardiopulmonary resuscitation. Results: After training, stress decreased and satisfaction about skills increased in the EG, whereas it remained the same in the CG ( P = 0.014 and P < 0.001, respectively). There was no significant change in self-efficacy. Analyses of video-recorded skills showed significant improvements in TSs and NTSs of the EG leaders after training, but not of the CG leaders ( P = 0.026, P = 0.038, respectively). The comparison of the evolution of the 2 groups concerning time to initiate cardiopulmonary resuscitation was not significantly different between the first and last simulation sessions. Conclusions: A simulation-based training with debriefing had positive effects on stress and satisfaction about skills of pediatric residents and nurses and on observed TSs and NTSs of the leaders during simulation sessions. A future study should assess the effectiveness of this training in a larger sample and its impact on skills during actual emergencies. Abstract : Supplemental digital content is available in the text.